-9=27-11b-13b

Simple and best practice solution for -9=27-11b-13b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9=27-11b-13b equation:


Simplifying
-9 = 27 + -11b + -13b

Combine like terms: -11b + -13b = -24b
-9 = 27 + -24b

Solving
-9 = 27 + -24b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '24b' to each side of the equation.
-9 + 24b = 27 + -24b + 24b

Combine like terms: -24b + 24b = 0
-9 + 24b = 27 + 0
-9 + 24b = 27

Add '9' to each side of the equation.
-9 + 9 + 24b = 27 + 9

Combine like terms: -9 + 9 = 0
0 + 24b = 27 + 9
24b = 27 + 9

Combine like terms: 27 + 9 = 36
24b = 36

Divide each side by '24'.
b = 1.5

Simplifying
b = 1.5

See similar equations:

| -28+p=7(p-10) | | Y^2-39y-42=0 | | 5.50c+8=35 | | 5(x-1)=x+25 | | 16(2-w)+11w=-13 | | -3(2x-3)=3(x-1) | | X+6=567+3-2 | | a+5+2a=5+3a | | 4x+3y=110 | | 3-w-(7w+12)=2(w-3) | | 4x=6z+76 | | 7*7-(8-2)= | | 6+4x=4x-5 | | 2(-x)-4+4x=x+5 | | 13+3x=5x-5 | | 9x+4x=2x+3 | | 13-(4-k)=5k+10-7 | | 37-X=14 | | 48-6x=4x-2 | | 8-g= | | X+150=.75(x+150) | | 3(4x-9)+12=9 | | 5t-7=5t | | 2a+14=-2(-a-3) | | -m-9=15 | | -I-17I= | | 3d-15=3(5+d) | | 11x+2x-9=24 | | 3(4x-9)12=9 | | -2(2a-7)=14-4a | | 3x+8x=9 | | 4x^2+25=7 |

Equations solver categories